Recidivism Among Convicted Drunk Drivers: Minnesota, 1982 ([Verlag nicht ermittelbar], 1987)
This data collection focuses on recidivism among persons convicted for driving while intoxicated. It contains information about the charging and sentencing of drunk driving offenders and repeat offenders. Variables include charge, conviction, sentence, number of alcohol and non-alcohol related violations, subsequent action, sex, age, and date of sentencing.